Model of Start-Up Business with Considering Household Spending using System Dynamics Approach - Renosori, Puti; Prasetyaningsih, Endang; Satori, Mohamad (Ann Publisher, 2024)
This study investigates a family-run start-up business in which the company's finances are not separate from the family’s finances. The start-up business owner relies on the company's finances to cover the household spending from the beginning because the owner is not paid by the company. As a result, the company fails to grow and is on the verge of bankruptcy. This study focuses on developing a start-up business model that considers household spending as a decision variable allowing it to grow and develop. The System Dynamics approach was chosen due to the complexity of the trade-offs between variables in a start-up business model. The Cassava meatball start-up business run by Madrasah is used as an example. The developed model simulates a variety of treatments, including giving debt to develop start-up businesses. However, this debt can be burdensome because the company must pay it. The findings indicate that the use of income to cover household spending at the beginning is inappropriate while providing debt to revive the startup must be sufficient and timely. The developed model is expected to assist start-up business owners in selecting a variety of alternative policies that will allow the business to grow, develop, and be sustainable.